Cutting Rate and Surface Characteristic Analysis in CNC Wire Electrical Discharge Machining of Aluminium Bronze - (:unkn) unknown (UNIV OSIJEK, TECH FAC, 2019)
In this study, cutting rate and surface characteristic analysis in wire electrical discharge machining of aluminium bronze were investigated. Cutting rate analyses were performed according to Taguchi L18 (2(1)x3(2)) orthogonal array. Machining parameters such as wire type, duration between two pulses (Br) and pulse time (AT) were used as control factors. Raw data obtained for cutting rate were converted to S/N ratio values. Optimum levels of the machining parameters for cutting rate were determined using analysis of signal-to-noise (S/N) ratio. Significant machining parameters and their percentage contributions on results were obtained using Analysis of Variance (ANOVA). Regression analysis was performed to model the relationship between cutting rate and machining parameters. Analyses of surfaces machined of workpiece using both two wires for minimum and maximum cutting rate were observed using scanning electron microscope (SEM) and surface roughness device.
Keywords: cutting rate; Scanning Electron Microscope (SEM); surface finish; Wire Electrical Discharge Machining (WEDM); PARAMETERS; WEDM; SPEED